PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KARTU PRABAYAR XL (STUDI KASUS MAHASISWA FISIP UNDIP SEMARANG) - Farah Nahlia; Agus Hermani DS (Universitas Diponegoro, 2016)
This research is motivated by the development of technology and the level of competition in this business field that is increasingly tight. One of the signs of market competitiveness can be seen in the last few years on how there’s declining on market share and selling volume of XL Prepaid Cards products in Indonesia. While the purpose of this research is to explain and elaborate the power of product quality, prices and promotion in influencing of Social and Political Science Faculty’s students decision to buy XL prepaid cards at Diponegoro University.The result shows that the variable of product quality have significant and positive impact toward purchasing decisions; the variable of prices have significant and positive impact toward purchasing decisions and the variable of promotion have significant and positive impact toward purchasing decisions.The conclusion from this research is that the quality products of prepaid cards XL rated mediocre; prices is considered cheap; promotion is considered good and the purchase decision is undervalued. The suggestions in this research is the XL prepaid card should pay more attention to the factors in terms of product quality regarding the power of networking and completeness of features, and then in terms of price on the value of the prepaid card and the pricing that is done in order to conform with the purchasing power of the public and in terms of promotion that is the accuracy of media promotions used and the frequency of the level of promotion done in order to increase the purchasing decision.